Comparison of postoperative pain and pain control techniques in uniportal and biportal VATS and open surgery patients - YILDIZELİ, BEDRETTİN; BATIREL, HASAN FEVZİ; BOSTANCI, KORKUT; YÜKSEL, MUSTAFA; LAÇİN, TUNÇ (MARMARA UNIV, FAC MEDICINE, 2021)
Objectives: Thoracotomy causes intense postoperative pain which may become chronic. Video-assisted thoracic surgery (VATS) leads to less postoperative pain compared with thoracotomy. In this study, we analyzed pain scores in patients who underwent lung resections with VATS or thoracotomy. Patients and Methods: Patients who underwent lung resections with uniportal, biportal VATS or thoracotomy between May 2015 - May 2017 were included in the study. Visual Analogue Scale (VAS) pain scores were recorded on postoperative day 1, 5 (or at discharge), 2nd week, 1st and 3rd months. Patients were classified in 3 groups, uniportal VATS (n=178), biportal VATS (n=15), thoracotomy (n=60). Demographics, resection type, mortality, morbidity and epidural catheter use were recorded. Results: Two hundred and fifty-three patients (average age was 57.3 +/- 12.7, 94 females) were included in the study. Median hospital stay was 5 days. Uniportal and biportal groups had significantly lower pain scores in all intervals compared with thoracotomy. No chronic pain was seen in VATS groups. Uniportal and biportal groups had similar pain scores at all times. Epidural use or size of specimen did not affect pain in VATS patients (p=0.18 vs p=0.68). Conclusion: Video-assisted thoracic surgery decreases the need for epidural patient control analgesia. Specimen size does not affect postoperative pain and chronic pain is rare.
Keywords: Thoracoscopy; Uniportal; Biportal; Postoperative analgesia; ASSISTED THORACOSCOPIC SURGERY; THORACOTOMY; RECOVERY; RESECTION